Pengaruh Academic Self-Efficacy Terhadap Student Engagement Pada Mahasiswa Psikologi - Aini Nadhiba Cinta Suryokusumo; Riza Noviana Khoirunnisa (Character Jurnal Penelitian Psikologi, 2026)
This study aims to analyze the influence of academic self-efficacy on student engagement in the Psychology Undergraduate Program at Surabaya State University. This study used a non-experimental quantitative approach with 174 students from the class of 2022 as subjects. Data collection was conducted online using two Likert scale instruments: the College Academic Self-Efficacy Scale and the Student Engagement Scale. Data analysis using linear regression showed a correlation coefficient (R) of 0.934; p < 0.001. The coefficient of determination (R²) of 0.872 indicates that academic self-efficacy contributes 87.2% effectively to student engagement. This means that the higher students' confidence in their academic abilities, the higher their engagement in the lecture process. The findings of this study are expected to serve as a basis for educational institutions in designing learning strategies that support increased student academic engagement